MODEL FLIPPED CLASSROOM BERBASIS LIVING VALUES EDUCATION PROGRAM SEBAGAI PENGUATAN PENDIDIKAN KARAKTER PESERTA DIDIK SEKOLAH DASAR - Mahilda Dea Komalasari; An-Nisa Apriani (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2021)
This study aims to determine the potential of the flipped classroom model based on living values education program to strengthen the character education of elementary school students. This research is a literature study using a qualitative descriptive approach by examining journals related to flipped classrooms and journals related to the living values education program. The results of these literature reviews will be used to identify the potential of a flipped classroom model based on a living values education program as a strengthening of character education for elementary school students. Sources of research data are secondary data sources. Data analysis in this literature review is content analysis. The results of this study indicate the potential for a flipped classroom model based on living values education program to strengthen the character education of elementary school students.